2014
DOI: 10.3349/ymj.2014.55.5.1260
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Initial Dexamethasone Treatment Combined with a Single High Dose of Intravenous Immunoglobulin for Primary Treatment of Kawasaki Disease

Abstract: PurposeTo investigate the clinical effects of a single high dose intravenous immunoglobulin (IVIG) combined with initial dexamethasone as a primary treatment on Kawasaki disease (KD).Materials and MethodsBetween January 2008 and December 2010, we reviewed the medical records of 216 patients with complete KD patients that were admitted to a single medical center. 106 patients were treated with a single high dose of IVIG (2 g/kg) alone and 110 patients received IVIG and dexamethasone (0.3 mg/kg per day for three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Kobayashi score (≥ 4-5 points) [ In addition, Inoue et al [48] reported that the combination of corticosteroids and IVIG as the first line therapy improved the clinical course and coronary artery outcome in their multicenter prospective study with 178 patients. However, the result of a multicenter randomized doubleblind placebo-controlled study by Newburger et al [49] , in which a single dose of methylprednisolone (30 mg/kg) was administrated did not agree with the result by Inoue et al [48] The result of another study of 216 patients in which dexamethasone (0.3 mg/kg per day for 3 d) was combined with IVIG showed no significant difference of coronary outcomes between groups [50] . Therefore, it is less likely that the administration of corticosteroids in combination with IVIG as the routine first line therapy in all Kawasaki disease patients reduces coronary artery lesions.…”
Section: Cut-off Pointsmentioning
confidence: 90%
“…Kobayashi score (≥ 4-5 points) [ In addition, Inoue et al [48] reported that the combination of corticosteroids and IVIG as the first line therapy improved the clinical course and coronary artery outcome in their multicenter prospective study with 178 patients. However, the result of a multicenter randomized doubleblind placebo-controlled study by Newburger et al [49] , in which a single dose of methylprednisolone (30 mg/kg) was administrated did not agree with the result by Inoue et al [48] The result of another study of 216 patients in which dexamethasone (0.3 mg/kg per day for 3 d) was combined with IVIG showed no significant difference of coronary outcomes between groups [50] . Therefore, it is less likely that the administration of corticosteroids in combination with IVIG as the routine first line therapy in all Kawasaki disease patients reduces coronary artery lesions.…”
Section: Cut-off Pointsmentioning
confidence: 90%
“…Although with regards to the use of steroids in KD, most of the studies have investigated the use of IVMP, Lim et al [76] studied the use of dexamethasone, a longer acting steroid in KD in a retrospective study. They reported better clinical outcomes on combined use of dexamethasone and high dose IVIG in terms of shorter febrile periods, lesser need for IVIG second dose and shortened hospital stay without worsening of cardiovascular outcomes [76].…”
Section: Treatmentmentioning
confidence: 99%
“…They reported better clinical outcomes on combined use of dexamethasone and high dose IVIG in terms of shorter febrile periods, lesser need for IVIG second dose and shortened hospital stay without worsening of cardiovascular outcomes [76]. Further larger and prospective studies are required to establish the efficacy of steroids as initial or second line treatment and also comparative efficacy of IVMP versus dexamethasone.…”
Section: Treatmentmentioning
confidence: 99%
“…The largest retrospective study of 1073 patients concluded that IVIg improves the initial severity of coronary lesions as measured by coronary artery aneurysm regression, but it does not provide protection against long‐term development of coronary artery aneurysms . A retrospective review ( n = 216) of IVIg as an adjunct to dexamethasone vs. IVIg therapy alone found combined therapy to be have a favourable profile, with less fever occurring, fewer IVIg courses required and shorter length of hospital stay . The dose of IVIg given in KD is standardized in Europe, the USA, UK and Australia, and consists of a single cycle of 2 g/kg as a bolus or divided into an infusion over 2–5 days .…”
Section: Clinical Indicationsmentioning
confidence: 99%